Incidence of viruses in highbush blueberry (Vaccinium corymbosum L.) in Serbia - Jevremović, Darko; Paunović, Svetlana; Leposavić, Aleksandar (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2016)
A large-scale survey for highbush blueberry (Vaccinium corymbosum L.) viruses in Serbia was performed from 2011 to 2015. A total of 81 leaf samples from 15 locations were collected and analyzed for the presence of 8 viruses. Serological ELISA assay was performed to determine the presence of: Blueberry scorch virus (BlScV), Blueberry shock virus (BlShV), Blueberry shoestring virus (BSSV), Blueberry leaf mottle virus (BLMoV), Tobacco ringspot virus (TRSV) and Tomato ringspot virus (ToRSV). All samples were tested for the presence of Blueberry red ringspot virus (BRRV) by PCR and for Blueberry mosaic-associated virus (BlMaV) by RT-PCR test. The analyses confirmed the presence of BlMaV in 8 (9.9%) samples and BRRV in 1 (1.2%) sample. No BlScV, BlShV, BLMoV, BSSV, TRSV or ToRSV viruses were detected in any of the analyzed samples.